Call to research in ventilator weaning and extubation in neurocritical care - Joseph, Arun; McWilliams, David; Rose, Louise (Intensive & critical care nursing, 2021)
[...]there is an urgent need to identify predictors of successful extubation in neurocritical care patients. Management of these factors requires careful consideration and forward planning to ensure appropriate availability of adequate resources such as respiratory physiotherapy to optimise airway clearance following extubation.Conclusion There is a significant and urgent need for further research to support identification of effective methods of weaning and extubation for neurocritical care patients. A plausible biological model of the relationship between cerebro-pulmonary interactions and pathophysiology of extubation failure that informs focussed assessment and treatment strategies could improve outcomes. [...]work to address the research questions proposed in Fig. 1 that focus on a solid biological model based on applied neuro-respiratory physiology followed by a clinical intervention model could promote evidence based practise in this area thereby improving patient outcomes Given the complex and multifactorial issues related to extubation in this patient population, moving forward an interdisciplinary and multi-professional approach to research may inform understanding of strategies that support extubation success in the future.Ethics statement This project comprised of a review of the current literature and no original work, therefore is not subject to any ethical considerations.Financial support and sponsorship Nil.Declaration of Competing Interest The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.